Exploring Joshua 7:1–5 through the lens of social contagion liability - Odo, Damian O. (Verbum et ecclesia, 2024)
Scholars of the Old Testament affirm that the book of Joshua through 2nd Kings is collectively called the deuteronomistic history. The literary unit of Joshua 7:1-5 is one the Locus Classicus of Old Testament. Obedience to God’s instruction underscores the theological intentionality expressed in this unified segment of Old Testament literature. This ancient Israelite literary exposition exposes inter-alia the misfortune that besets the entire people of Israel as a result of Achan’s moral transgression. The consequence of Achan’s antisocial behaviour was so contagious that it spread across to the entire populace of Israel as they were humiliated and defeated in a battle by the warriors of Ai. This pericope has been studied in various perspectives by commentators and scholars of the Old Testament; however, a survey of available literature shows that it has not been explored by scholars from the orbit of social contagion liability. Therefore, this article intends to engage the literary unit, employing the lens of social contagion liability Intradisciplinary and/or interdisciplinary implications: This study engaged the literary unit of Joshua 7:1-5 from the orbit of social contagion liability. It argues that Achan’s anti-social behaviour spread to the entire populace of Israel and got them contaminated and exposed to misfortune because it has the characteristics of social contagion liability. The study contributed to Old Testament Exegesis, sociology and social contagion study.